Biodiversity and ecosystem services in cultural landscapes of Germany and Japan - Sasaki, Keiko; Justus Liebig University Giessen (My University, 2023)
This cumulative dissertation takes a comparative approach to studying the spatial patterns of biodiversity and ecosystem services in agricultural landscapes of Germany and Japan. In both countries, biodiversity and ecosystem services maintained by the respective traditional farming systems are declining due to agricultural intensification and land abandonment. Landscape associations of bird species that are typical in agricultural landscapes of Germany and Japan were analyzed jointly, while spatial associations of ecosystem services were investigated using data from Japan only owing to the different frameworks used by public institutions for gathering data. Findings from the latter study were compared to published results from the literature in Europe. Both studies were carried out at the national level. Distribution data on bird species were obtained from nationwide monitoring programs, and metrics of landscape structure and ecosystem services linked to agroecosystems were calculated based on spatial datasets and public statistics using a geographical information system. The first chapter demonstrates that farmland bird diversity responds to the proportions of farmland cover and semi-natural habitat cover in a similar way between Germany and Japan. The results also suggest that landscape associations can vary according to the countries. Woodland edge density had a pronounced effect on species numbers in Germany where farmland dominates. In contrast, farmland cover was more relevant in Japan than in Germany; in Japan, where forests dominate, the effect of woodland edge density was only marginal. The importance of open habitats and landscape heterogeneity for maintaining farmland bird diversity was supported by these findings. In the second chapter, landscapes in Japan specializing either in commodity production or in cultural services and habitat features were identified based on indicators for agricultural ecosystem services and farmland biodiversity. The latter landscapes coincided with areas at risk of land abandonment. The spatial aggregation of biodiversity and culturally valuable resources on marginal land, where traditional farming systems are likely to persist, underlies the importance of conserving the structural features of traditional farming systems. To conclude, this dissertation supports the notion that landscape structure, biodiversity, and ecosystem services are linked significantly, and that such links apply generally in Germany and Japan.
Keywords: agricultural intensification; farmland abandonment; landscape structure; social-ecological systems; traditional land uses; ddc:333.7; ddc:570